The Role of AMACR, CD10, TMPRSS2-ERG, and p27 Protein Expression Among Different Gleason Grades of Prostatic Adenocarcinoma on Needle Biopsy. (August 2020) - Gülhan, Özdemir; Mahi, Balcı
Objective: We examined the immunohistochemical expression of α-methyl acyl coenzyme A racemase (AMACR), CD10, TMPRSS2-ERG, and p27 in prostate adenocarcinoma tumors with different Gleason growth patterns and nonneoplastic prostate tissues to elucidate their roles in prostate carcinogenesis and histological aggressiveness. Material and Methods: In total, 80 archival core biopsy tissues diagnosed as prostate carcinoma, benign prostate hyperplasia, and atrophy cases were included. Immunoreactivity was evaluated by calculating the percentage of positively stained cells and the staining intensity. The mean values and test of significance were obtained using the Kruskal-Wallis test. Results: We obtained mostly intense immunoreactivity for AMACR, CD10, and ERG in adenocarcinomas. Although no significant differences were noted regarding AMACR and ERG expression, samples with Gleason growth patterns 3 and 5 tended to be strongly positive for ERG. Pattern 3 tumors exhibited the weakest positivity for CD10. The p27 expression was strong and diffuse in nonneoplastic prostate tissues. The loss of p27 expression was more frequent for pattern 5 tumors. Conclusion: ERG and AMACR were powerful markers to detect cancer. Especially, ERG is evident in early tumors may reflect its interaction with functional androgen receptors in cancer initiation. Pattern 5 tumors associated with stroma may have been exposed to more stromal substrates and upregulate their CD10 content as a protein degrader. We suggest that CD10 expression is associated with an increasing tumor grade. Decreased concentrations of p27 protein might be implicated in prostate carcinogenesis and may be a useful immunohistochemical adjunct in predicting histological aggressiveness.